PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2015-2017) - Rita Lia Novita; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis research was conducted to analyze the effect of corporate financial performance on company value with Corporate Social Responsibility as a moderating variable. The sample in this company is a manufacturing company in 2015-2017 which is included in the consumer goods industry sub sector. The analytical method used is multiple linear regression with SPSS 22 software for windows. Based on the predetermined sample criteria there are 23 companies that meet the criteria. From the results of testing, the results of testing simultaneously show that simultaneously the ROA variable and disclosure of CSR affect the value of the company. Partial test results show that partially the ROA_CSR variable has an effect on company value, then H2 is accepted, the coefficient value of 360,477 shows that the CSR variable is a moderating variable that is able to moderate the effect of ROA on firm value.